2017
DOI: 10.1111/jeb.13210
|View full text |Cite
|
Sign up to set email alerts
|

How the environment shapes animal signals: a test of the acoustic adaptation hypothesis in frogs

Abstract: Long-distance acoustic signals are widely used in animal communication systems and, in many cases, are essential for reproduction. The acoustic adaptation hypothesis (AAH) implies that acoustic signals should be selected for further transmission and better content integrity under the acoustic constraints of the habitat in which they are produced. In this study, we test predictions derived from the AAH in frogs. Specifically, we focus on the difference between torrent frogs and frogs calling in less noisy habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 80 publications
(152 reference statements)
2
46
0
1
Order By: Relevance
“…On the other hand, call duration is not phylogenetically constrained. Previous studies have found individual, intraspecific and interspecific variation of temporal traits such as call duration, call rate and pulse rate to be correlated with environmental temperature (Bellis, ; Blair, ; Gillooly & Ophir, ; Goutte et al., ; Köhler et al., ; Zweifel, ). Unfortunately, analyses of correlations between acoustic variables and environmental temperature were precluded by (a) the lack of associated temperature data of most recordings and (b) the different sample sizes of recordings available for each species, some of which were represented by recordings spanning several dates and geographic locations, rendering an average temperature estimation uninformative.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, call duration is not phylogenetically constrained. Previous studies have found individual, intraspecific and interspecific variation of temporal traits such as call duration, call rate and pulse rate to be correlated with environmental temperature (Bellis, ; Blair, ; Gillooly & Ophir, ; Goutte et al., ; Köhler et al., ; Zweifel, ). Unfortunately, analyses of correlations between acoustic variables and environmental temperature were precluded by (a) the lack of associated temperature data of most recordings and (b) the different sample sizes of recordings available for each species, some of which were represented by recordings spanning several dates and geographic locations, rendering an average temperature estimation uninformative.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the high‐pitched calls of some relatively large species could be an adaptation to outcompete the masking interference of torrent noise. As background noise data were missing for all calls, future studies could benefit from collecting data on the intensity and bandwidth of waterfall and rapids noise (Goutte et al., , ; Narins et al., ; Schwartz & Bee, ), as well as information about height of calling perches (Kubicki, ; Señaris & Ayarzaguena, ) and standardized measurements of call amplitude along the background noise gradient (Schwartz & Bee, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sampled populations are separated with white dashed lines. Equally color populations share genetic ancestry (modified from Oklander et al 2017) [Colour figure can be viewed at wileyonlinelibrary.com] 2010; rails: Rek & Kwiatkowska, 2016 and torrent frogs: Goutte et al, 2018). Evidence gathered over the years provided partial support to this theoretical framework (reviewed in Ey & Fisher, 2009), in part because other factors beyond vegetation type and/or environmental sound come into play influencing vocalization structure.…”
Section: Introductionmentioning
confidence: 99%